Isolation and Selection of Rhizobium Tolerant to Pesticides and Aluminum from Acid Soils in Indonesia - Martani, Erni; Margino, Sebastian; Indradewa, Didiek; Supriyo, Agus (UNIVERSITY OF LAMPUNG, 2011)
Application of Rhizobium as inoculum in acid soil requires specific characters, namely high tolerance to pesticide residues, soil acidity, and high concentration of Aluminum. This study was conducted to isolate Rhizobium having these characters. Inspite of acid soils from Kalimantan, Sumatra, Sulawesi and Java; root nodules of legumes planted in those regions were used as source of isolates. Rhizobial isolation was done using direct isolation andenrichment technique. A paper disc diffusion technique was used in selecting tolerance to pesticides. The selected isolates were examined the tolerance to pH, Al, and ability to form root nodule with soybean. From soil analysis, it could be seen the correlation between pH value and Al concentration. It means that the lower pH value the higher Al concentration. The number of Rhizobium isolates and its tolerance to paraquat was depended on soil type. From 173 strains of isolated Rhizobium, 24 strains were tolerance to pesticides and Aluminum. They were able to grow in wide range of pH, namely 3 – 8, or some of them in 5 - 8. Around 92% of the selected bacteria could form root nodules with soybean plant in different number and size. Hopefully, these isolates can be applied in the pesticide polluted agricultural lands, especially in acid soils with high concentration of Al, and it can also increase soybean production.Keywords: Acid soils, aluminium, Rhizobium, pesticides